Students' critical thinking skills based on the STEAM approach: The issue of waste recycling and ecology - Pelamonia, Johanes; Ginting, Cristina; Kempa, Evelin; Tobing, Devi; Leasa, Marleny (Education and Development Research, 2025)
The critical thinking skills of elementary school students are still relatively low, even though these skills are essential for facing the demands of the 21st century and global challenges. The low level of critical thinking skills is a significant problem in the learning process, so an innovative approach is needed to address it. This study aims to analyze the effectiveness of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach in improving the critical thinking skills of elementary school students. This study was conducted at an elementary school in Ambon City at the 6th grade level that has implemented STEAM learning, involving 20 students as samples. Qualitative methods and a phenomenological approach were chosen to explore the students' experiences, perceptions, and learning processes in depth. Fifteen essay questions based on Facione's (1990) indicators were used to measure students' critical thinking skills, along with semi-structured interviews and documentation of STEAM project results as evidence of implementation. Data analysis was carried out through the stages of data reduction, data presentation, and verification to ensure the validity of the findings. The results showed that the STEAM approach significantly improved critical thinking skills in interpretation, analysis, explanation, inference, and evaluation. However, students still needed further assistance in independently managing the critical thinking process in self-regulation. In conclusion, STEAM-based learning has been proven effective in stimulating critical thinking skills through contextual and collaborative learning models relevant to real-life situations and encouraging student cooperation.